DISPARITAS HARGA CABAI RAWIT (Capsicum frutescens L.) ANTAR WAKTU DAN ANTAR WILAYAH DI INDONESIA - Putri, Indira Rosandry Ajeng Syah; Harianto; Rosiana, Nia (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
Chili is a strategic food commodity in Indonesia that significantly impacts inflation, particularly in the volatile foods category. In recent years, price disparities of chili have raised concerns due to marked inequalities across regions. This study aims to analyze the price disparity of chili over time and between regions in Indonesia while identifying contributing factors. The research utilizes descriptive statistical methods, calculating the coefficient of variation of chili prices at the retail level using data from the Central Statistics Agency (BPS). The findings reveal that the average price disparity over time remains high, peaking in 2021. Paradoxically, production centers exhibit high disparities due to the seasonal nature of production, uneven distribution, and the impact of the COVID-19 pandemic. Conversely, non-production centers recorded lower disparities. Price disparity between regions consistently exceeded government targets during the study period. Key influencing factors include geographical conditions, imbalanced access to distribution infrastructure, and dependency on external supply. Inter-provincial trade of chili often faces high distribution costs, further widening the price gap between production and consumption centers. To address these issues, inclusive and sustainable policies are essential. These policies should focus on improving distribution infrastructure and optimizing the chili supply chain to achieve even price stability nationwide.